INVESTIGATION OF SHORT-TERM CHEMICAL CHANGE IN STABLE RUTHENIUM ADDED TO RAINWATER THROUGH X-RAY ABSORPTION FINE STRUCTURE ANALYSIS. Issue 13 (9th September 2022) - Unno, Yusuke; Takeda, Akira; Takaku, Yuichi
Abstract: Radioactive ruthenium may be accidentally released from spent nuclear fuel reprocessing plants to the surrounding environment. To obtain basic information regarding the effect of radioactive ruthenium on the environment, we investigated changes in the source form of stable ruthenium added to rainwater through X-ray absorption fine structure analysis. Ruthenium tetroxide (RuO4 ), ruthenium dioxide (RuO2 ), ruthenium nitrosyl nitrate (Ru(NO)(NO3 )3 ) and ruthenium chloride (RuCl3 ) were employed as test sources. The Ru K-edge X-ray absorption near edge structure spectra acquired immediately after addition to ultrapure water differed among various sources. With RuO4 addition, a black deposit was observed 1 d after addition, and the spectrum was similar to that of RuO2 . For RuO2, Ru(NO)(NO3 )3 and RuCl3, no variances were observed between the spectra acquired immediately after addition and 1 d after addition. These results indicate that the chemical forms of RuO2, Ru(NO)(NO3 )3 and RuCl3 did not change within a 1-d span in rainwater.